2003
DOI: 10.1128/iai.71.9.4883-4890.2003
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Campylobacter jejuni Cytolethal Distending Toxin Subunits CdtA and CdtC with HeLa Cells

Abstract: Campylobacter jejuni produces a toxin, called cytolethal distending toxin (CDT), which causes direct DNA damage leading to invocation of DNA damage checkpoint pathways. The affected cells arrest in G 1 or G 2 and eventually die. CDT consists of three protein subunits, CdtA, CdtB, and CdtC, with CdtB recently identified as a nuclease. However, little is known about the functions of CdtA or CdtC. In this work, enzyme-linked immunosorbent assay-based experiments were used to show, for the first time, that both Cd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
122
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(137 citation statements)
references
References 34 publications
13
122
1
1
Order By: Relevance
“…The normal route for triggering the cytolethal activity of CDT requires the presence of all three CDT subunits. Recent reports indicate that CdtA and CdtC are the binding subunits of the CDT holotoxin (5,14,16). These data are supported by structural analysis of the CDT Hd holotoxin, indicating that CdtA Hd and CdtC Hd possess structural folds that resemble those of the ricin B chain (17).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…The normal route for triggering the cytolethal activity of CDT requires the presence of all three CDT subunits. Recent reports indicate that CdtA and CdtC are the binding subunits of the CDT holotoxin (5,14,16). These data are supported by structural analysis of the CDT Hd holotoxin, indicating that CdtA Hd and CdtC Hd possess structural folds that resemble those of the ricin B chain (17).…”
Section: Resultssupporting
confidence: 63%
“…Unlike the CdtAC heterodimer, individual CdtA Hd and CdtC Hd subunits failed to block the action of holotoxin, suggesting that the CdtAC heterodimer is the functional cell surface-binding component of CDT (5). Recently, Lee et al demonstrated that CdtA and CdtC of C. jejuni (CdtA Cj and CdtC Cj , respectively) bound independently to HeLa cells and exhibited competitive binding for one another, suggesting that these subunits bind to the same cell surface structure (14).…”
mentioning
confidence: 99%
“…Consistent with their proposed roles as binding subunits, CdtA and/or CdtC increase the ability of CdtB to associate with host cells and greatly enhance intoxication (7,(17)(18)(19)(20)(21)(22)(23)(24)(25). The identification of ricin-like lectin domains in CdtA and CdtC from structural and biochemical data first suggested that these subunits may interact with carbohydrates on the cell surface (13,26,27).…”
mentioning
confidence: 63%
“…It is not currently known which activity is of greater importance, and this may depend on the specific toxin and/or the host target cell type (12,14). CdtB enzymatic activity induces cell cycle arrest predominantly at the G 2 /M transition, resulting in cellular distension and ultimately cell death (5,15,16).Consistent with their proposed roles as binding subunits, CdtA and/or CdtC increase the ability of CdtB to associate with host cells and greatly enhance intoxication (7,(17)(18)(19)(20)(21)(22)(23)(24)(25). The identification of ricin-like lectin domains in CdtA and CdtC from structural and biochemical data first suggested that these subunits may interact with carbohydrates on the cell surface (13,26,27).…”
mentioning
confidence: 86%
“…Very limited data are available about the function of CdtA and especially of CdtC. Many studies find that both CdtA and CdtC are capable of binding to the cellular membrane and some suggested that they might share the same receptor [15][16][17][18] . Reports indicating that antibodies raised against CdtC were protective against CDT toxicity corroborated these findings.…”
Section: Cloning and Protein Expression Ofmentioning
confidence: 99%